Multiplex Cytokine Analysis of Aqueous Humor in Juvenile Idiopathic Arthritis-Associated Anterior Uveitis With or Without Secondary Glaucoma - Bauer, Dirk; Kasper, Maren; Walscheid, Karoline; Koch, Jörg M.; Müther, Philipp S.; Kirchhof, Bernd; Heiligenhaus, Arnd; Heinz, Carsten (Frontiers in Immunology, 2018)
Abstract Patients with juvenile idiopathic arthritis often develop chronic anterior uveitis (JIAU). JIAU patients possess a particularly high risk for developing secondary glaucoma when inflammatory inactivity has been achieved. By using multiplex bead assay analysis we assessed levels of pro- and anti-inflammatory cytokines, chemokines, or metalloproteinases in the aqueous humor (AH) of patients with clinically inactive JIAU with (JIAUwG) or without secondary glaucoma (JIAUwoG), or from patients with senile cataract as controls. Laser-flare photometry analysis prior to surgery showed no significant differences between JIAUwG or JIAUwoG. Compared with the control group, levels of IL-8, MMP-2, MMP-3, MMP-9, SAA, TGFb1, TGFb2, TGFb3, and TNF-a in the AH were significantly higher in patients with clinically inactive JIAUwG or JIAUwoG. Samples from JIAwoG patients displayed significantly higher levels of SAA (P<0.0116) than JIAUwG patients. JIAUwG patients showed an increased level of TGFb-2 in AH samples compared to JIAUwoG (P<0.0009). These molecules may contribute to the clinical development of glaucoma in patients with JIAU.